Immune-related proteins detected through iTRAQ-based proteomics analysis of intestines from Apostichopus japonicus in response to tussah immunoreactive substances. Issue 74 (March 2018) - Mi, Rui; Sun, Yongxin; Li, Jianguang; Ma, Shuhui; Wen, Zhixin; Li, Xuejun; Meng, Nan; Li, Yajie; Du, Xingfan; Li, Shuying
Abstract: Apostichopus japonicus is a species of sea cucumber that is extensively bred as a marine delicacy because of its high nutritive and medicinal value. Immunostimulants are usually used to enhance the immunity of sea cucumber against diseases, but the physiological function of immunostimulants is poorly understood. In this study, we fed A. japonicus individuals with a diet supplemented with different concentrations of tussah immunoreactive substances (TIS), and then subjected their intestines to iTRAQ-based proteomic analysis. A total of 51 differentially expressed proteins were detected in response to TIS, 13 proteins were upregulated, while 38 proteins were reduced. These proteins are involved in phagocytosis, tissue protection, cell apoptosis and energy metabolism. Among these 51 proteins, 7 proteins (GLO2, ACOX, CTTN, MARK, FADD, CSTA and CASP6) related to immunity with functional annotation in sea cucumber were further analyzed. In addition, the upregulated expression of 4 immune-related proteins (GLO2, ACOX, CTTN and MARK) was validated by q RT-PCR. The findings of this study gave further insight into the mechanism by which TIS might enhance the immunity of A. japonicus . Highlights: It is the first time to explore the proteomic profiles in sea cucumber by using TIS as immunostimulants via iTRAQ technique. TIS can significantly affect the expression of immune-related proteins in the intestines of sea cucumber. The immune-related proteins involved in cell phagocytosis and tissue protection were validated by q RT-PCR.